ELUM: A spatial modelling tool to predict soil greenhouse gas changes from land conversion to bioenergy in the UK. (October 2016) - Pogson, Mark; Richards, Mark; Dondini, Marta; Jones, Edward O.; Hastings, Astley; Smith, Pete
Abstract: The ELUM Software Package spatially predicts the net soil greenhouse gas balance of land-use change to grow energy crops in the UK up to 2050. It is able to support a range of analyses of bioenergy, and was developed in consultation with anticipated users. Results can be obtained according to specific interests, viewed in the graphical interface and exported for a variety of purposes. The functionality of the software is demonstrated through different case studies, which show an array of applications. Highlights: ELUM models soil greenhouse gas balance of bioenergy land-use change in UK to 2050. It is based on the ECOSSE model, but quick and easy to use, with added features. It is able to support life-cycle assessments and policy making for bioenergy. Consultation with anticipated users guided usability and functionality. Greenhouse gas balance is highly dependent on initial land use and new energy crop.